2008
DOI: 10.1097/inf.0b013e31817cf76f
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia After Implementation of the Pneumococcal Conjugate Vaccine Program in the Province of Quebec, Canada

Abstract: Results are reassuring as to the effectiveness of the pneumococcal vaccination program in Quebec.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
2
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 14 publications
6
50
2
3
Order By: Relevance
“…The direct effect on pneumonia has been confirmed by review of records in children less than 1 year of age in one group health setting in Washington State [14]. Long-term trends from Quebec have also confirmed a significant reduction in lobar pneumonia in infants following the introduction of PCV7 in that Canadian province [15]. A similar impact has been demonstrated in Australia in children [16].…”
Section: The Clinical Spectrum and Burden Of Pneumococcal Diseasesupporting
confidence: 52%
“…The direct effect on pneumonia has been confirmed by review of records in children less than 1 year of age in one group health setting in Washington State [14]. Long-term trends from Quebec have also confirmed a significant reduction in lobar pneumonia in infants following the introduction of PCV7 in that Canadian province [15]. A similar impact has been demonstrated in Australia in children [16].…”
Section: The Clinical Spectrum and Burden Of Pneumococcal Diseasesupporting
confidence: 52%
“…Another study revealed a significant decline of 72% for lobar pneumonia admissions in Canadian children [12]. A population-based study in Israel demonstrated the effectiveness of PCVs was 40.7%, for the control of alveolar pneumonias [13].…”
Section: Discussionmentioning
confidence: 99%
“…2 Similarly, the 9-valent PCV formulation prompted similar immune responses when used in 3-and 4-dose schedules, 17 and the 10-valent vaccine has been shown to provide similar protection against IPD when given using 2+1 or 3+1 schedules. 18 Subsequent studies have confirmed that 2+1 PCV7 schedules can be highly effective at a population level in preventing IPD, [19][20][21][22] pneumonia, 23,24 and OM. 25 Early data on the impact of a 2+1 schedule of PCV13 are available, 26 and the effects of 2+1 schedules have been sufficiently encouraging for the World Health Organization 12 and national governments 11,26 to support use of a 2+1 schedule for PCV13.…”
Section: Resultsmentioning
confidence: 99%